Building Resilience and Competence in Bachelor Nursing Students: A Narrative Review Based on Social Cognitive Theory - Elisabeth Wille; Helene Margrethe Storebø Opheim; Daisy Michelle Princeton; Sezer Kisa; Kari Jonsbu Hjerpaasen (Nursing Reports)
Background/Objectives: In contemporary nursing education, clinical competence and psychological resilience are both essential; however, they are often treated as separate outcomes. Clinical placements are a central component of nursing education, and often expose students to high levels of stress, emotional challenges, and complex clinical demands. Building both clinical competence and psychological resilience during this phase is crucial to preparing students for the realities of professional practice. This narrative review, grounded in Bandura’s social cognitive theory (SCT), explores how educator behaviors, teaching strategies, and learning environments interact to influence both domains in undergraduate nursing students. Methods: A comprehensive search was conducted in PubMed, CINAHL, and PsycINFO for peer-reviewed articles published between 1 January 2000 and 2 May 2025. Relevant studies were thematically analyzed and were guided by Bandura’s SCT constructs, including observational learning, self-efficacy, and reciprocal determinism. No formal study appraisal was conducted due to the narrative nature of the review. Findings: Nineteen studies were included in the review. The findings highlight that reflective practices, structured feedback, peer learning, and strategies to build self-efficacy are central to building resilience and competence. Supportive educator behaviors such as mentoring, emotional support, and professional role modeling, were strongly associated with increased student confidence, emotional regulation, and adaptability. Psychologically safe clinical learning environments further enhanced self-efficacy and active engagement. In contrast, unsupportive or inconsistent environments were linked to student stress, disengagement, and reduced performance. Conclusions: This review highlights the need to move beyond traditional competency-based models toward an integrated approach that equally values psychological preparedness and resilience. Findings suggest a shift toward emotionally and socially integrated clinical education.